Bed Planting A New Crop Establishment Method for Wheat in Rice-Wheat Cropping System - Mollah, MIU; Bhuiya, MSU; Kabir, MH (Journal of Agriculture & Rural Development, 2010)
An experiment was conducted at the Bangladesh Rice Research Institute, Gazipur during Rabi season 2001-02 and 2002-03 to determine the effects of bed width, plant row number bed-1 and seed rate on the agro-economic productivity of wheat under bed planting in rice-wheat cropping system. Bed planting in 70, 80 and 90 cm wide beds with two and three plant rows bed-1 along with conventional method and 60, 90, 120 and 150 kg ha-1 seed rates were tested. Seventy-centimeter wide beds increased grain yield of wheat up to 21% over conventional method. It increased the number of panicles m-2, number of grains panicle-1 and 1000-grain weight of wheat. Sterility percentage was lower in bed than conventional method. Weed infestation was less in bed planting. It saved 41-48 % irrigation water. The cost of cultivation was lower and gross return, gross margin and benefit-cost ratio were higher in bed planting than conventional method. Key words: Bed planting, wheat, crop establishment. DOI: 10.3329/jard.v7i1.4418 J Agric Rural Dev 7(1&2), 23-31, June 2009